2016
DOI: 10.1002/macp.201500542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Shear-Inducedβ-Form Crystal Formation of iPP

Abstract: The conformation of a helical type polymer chain in the crystalline phase prefers the state with lower energy. The molecular simulation of the melting behaviors of α and β isotactic poly(propylene) (iPP) crystals with ultrafast heating shows that the ratio of right‐handed and left‐handed helix stays at 50% in α‐iPP and changes from 100% to 50% in β‐iPP before and after melting. Till date, the formation of β form crystal in iPP has not been understood well together with the mechanism of the crystallization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Semicrystalline polymers are always subjected to crystallization in certain flow fields during polymer-processing procedures due to the complicated, strong force fields, which will directly influence the microstructures and final mechanical properties of the polymers. Over the past decades, both experimental and theoretical efforts have been made to understand the molecular mechanism of flow-induced crystallization (FIC). It is widely accepted that flow (shear or tensile force fields) can substantially increase crystallization rates, that is, shorten the crystallization time of isothermal crystallization ,, or raise the crystallization temperature of nonisothermal crystallization. , The widely recognized explanation for the acceleration of crystallization kinetics is that flow brings about the orientation and stretching of chains in the melt, leading to less chain conformation and lower melt entropy relative to the quiescent melt, which will reduce the nucleation barrier and result in the enhancement of the nucleation rate as well as the overall crystallization rate. ,, The type of flow, the intensity of flow, and the flow time will affect the crystallization process. The extent of chain deformation, including segmental orientation and chain stretching, is closely related to the flow intensity, that is, the shear rate γ̇ in shear flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semicrystalline polymers are always subjected to crystallization in certain flow fields during polymer-processing procedures due to the complicated, strong force fields, which will directly influence the microstructures and final mechanical properties of the polymers. Over the past decades, both experimental and theoretical efforts have been made to understand the molecular mechanism of flow-induced crystallization (FIC). It is widely accepted that flow (shear or tensile force fields) can substantially increase crystallization rates, that is, shorten the crystallization time of isothermal crystallization ,, or raise the crystallization temperature of nonisothermal crystallization. , The widely recognized explanation for the acceleration of crystallization kinetics is that flow brings about the orientation and stretching of chains in the melt, leading to less chain conformation and lower melt entropy relative to the quiescent melt, which will reduce the nucleation barrier and result in the enhancement of the nucleation rate as well as the overall crystallization rate. ,, The type of flow, the intensity of flow, and the flow time will affect the crystallization process. The extent of chain deformation, including segmental orientation and chain stretching, is closely related to the flow intensity, that is, the shear rate γ̇ in shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…For the FIC, the acceleration effect on the crystallization kinetics of polymer melts is mostly observed in single polymers, including flexible polymers ,,,, and rigid materials ,, and also some multicomponent systems. , However, the flow-induced reduction of the crystallization rate of polymer melts is rarely reported. Sun et al found that shear flow decreased the crystallization rate of the high-impact polypropylene with a high content of the interfacial compatibilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the crystalline forms, the α-form is by far the most common and stable modification, which can be obtained through conventional processing. , By contrast, the β- and γ-forms are metastable phases. To obtain a large amount of β- or γ-forms in iPP requires special crystallization conditions. For example, the β-form can only be induced using a high crystallization temperature gradient, or applying a flow on a supercooled melt, ,, or adding active β nucleating agents (β-NAs). Among these methods, the addition of β-NAs is the most effective and accessible method to obtain abundant β-iPP. Different from the β-form, the γ-phase can be observed in some special PP polymers, such as very low molecular weight PP, , propylene copolymers with a small number of 1-olefine counits, , PP with chain irregularities and stereo- or regiodefects, or a high-pressure crystallized iPP. For Ziegler–Natta isotactic polypropylene (ZN-iPP) with a high stereotacticity, elevating pressure is the most frequently used way to obtain a high fraction of γ-form .…”
Section: Introductionmentioning
confidence: 99%
“…However, the controllable preparation of desired polymorphic structure in PP is challenging. One reason is that the interactions among its crystal phases are rather complex; for example, the formation of a kind of crystal form may be favorable or unfavorable for the formation of other ones. , Another reason is that the polymorphic structure of iPP is affected by several external factors, such as flow, pressure, and temperature during polymer processing (e.g., extrusion, injection, and blowing molding). ,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation